Pendidikan Moral pada Gamers Society Perspektif Pendidikan Islam - Angga Mahardika Putra; Muhammad Miftah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid development of the gaming industry and gamer community in the current digital era has raised concerns about the negative impacts that have the potential to affect the morals and behavior of game players, especially teenagers. This article examines the perspective of Islamic Religious Education in instilling moral values ​​in the gamer community. Using a qualitative approach and literature study, this research explores the principles of Islamic teachings that are relevant to character formation and healthy gaming ethics. The research results show that Islamic Religious Education offers comprehensive moral guidelines in guiding the gamer community. Principles such as fairness, patience, tolerance and self-control are important foundations in creating a positive playing environment and avoiding negative behavior such as addiction, violence and discrimination. Apart from that, Islamic teachings also emphasize the concept of moderation and balance in entertainment activities, as well as prioritizing social responsibility and respect for others. This research contributes to the enrichment of Islamic education, especially in responding to moral challenges arising from the development of technology and digital culture. The perspective of Islamic religious education presented can be a reference for understanding and guiding the gamers society in a way that is relevant to the times, reinforced by the Social Learning Theory proposed by Albert Bandura, which is useful for developing a code of ethics for playing games that is in line with religious principles. Thus, the gamer community can enjoy playing games in a healthy and responsible manner, while strengthening their moral character in accordance with Islamic teachings.